Optimisation of agro-technologies for sustainable development of agriculture in Uzbekistan - Yusupov Sherzod; Azizov Inomdjon; Khaydarov Ramozon; Inadullaeva Sevara; Kholmirzayev Sattar (BIO Web of Conferences, 2025)
The analysis of food security problems in the Republic of Uzbekistan, considered in the context of global challenges and the diversity of strategies for the development of the agro-industrial complex is presented in this paper. Particular attention is paid to assessing the results of the ongoing agrarian reforms, analysing the unique agro-climatic conditions of Uzbekistan, and identifying the key factors hindering the sustainable development of agriculture. As part of the study, experimental work was carried out to examine the effectiveness of various agro-technological techniques and methods, including irrigation systems, fertiliser application and tillage methods, using modern equipment. The results showed that drip irrigation and organic fertilisers, combined with minimum tillage, provide significant savings in water resources, improved soil fertility and increased yields. Based on the analysis, the necessity of transition to intensive farming with the use of conservation technologies has been identified.